Respuesta :

Gyzmo

Answer:

f(-4) = -120

Step-by-step explanation:

So we know that f(x) = 11x - 5x² + 4, and we are trying to solve for f(-4). To solve for f(-4), we plug -4 for x in the equation of f(x). In other words, change all x's into -4 in the equation 11x - 5x² + 4 and then solve.

f(x) = 11x - 5x² + 4

Plug in -4 for x.

f(-4) = 11(-4) - 5(-4)² +4

Simplify. 11(-4) = -44,   5(-4)² = 5(16) = 80.

f(-4) = -44 - 80 + 4

Solve.

f(-4) = -120

The answer is f(-4) = -120.

I hope this helps. If you need any clarifications, feel free to ask. Happy studying. :)

ACCESS MORE